TELAAH NILAI-NILAI PENDIDIKAN MODERASI BERAGAMA DALAM KITAB MAFAHIM YAJIBU AN-TUSHOHAH KARYA SAYYID MUHAMMAD ALAWI AL-MALIKI AL-HASANI - Samsul Arifin; Ali Ahmad Yaenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
Sayyid Muhammad Alawi Al-Maliki Al-Hasani is a prominent scholar in the Islamic world who hailed from Mecca, Saudi Arabia. He is recognized as one of the most respected figures within Ahlus Sunnah wal Jama'ah, particularly in the fields of hadith, Sufism, and other classical Islamic sciences. As a descendant of the Prophet Muhammad (SAW) through his grandson Hasan, Sayyid Al-Maliki is considered one of the great scholars of the 20th century. He made significant contributions to the Islamic world, particularly in spreading values of moderation, tolerance, and compassion. Sayyid Al-Maliki is known for promoting a wasathiyah (moderate) approach to Islam, rejecting extremism and blind fanaticism—whether from overly literalist or excessively liberal groups. This research is a library study, as it involves collecting data through documentation derived from written sources. In this context, the researcher seeks to deeply understand the texts and thought framework of Sayyid Muhammad Alawi Al-Maliki Al-Hasani, particularly regarding the values of moderate Islam. The findings of the study reveal that the book Mafahim Yajibu An-Tushohah contains numerous values of religious moderation that are highly relevant to the social and religious life in Indonesia. These values include tolerance (tasamuh), balance (wasathiyah), inclusivity, and brotherhood (ukhuwwah Islamiyyah and ukhuwwah insaniyyah), among others.